The Second Life Virtual Environment in Written Communicative Competence among Secondary Education Students (Docentes 2.0 Journal, 2026)
The rapid development of ICTs has significantly impacted various sectors, including education. Therefore, the objective of this research was to demonstrate whether the use of the Second Life virtual environment improves the development of the competence “Writes various types of texts in their mother tongue” among students at the Ollantay Educational Institution. The study was conducted within the positivist paradigm, under the hypothetico-deductive method, with a quantitative approach and a one-group pre-experimental pretest-posttest design, with descriptive-comparative scope. A non-probabilistic sample of 29 students was selected. Two main variables were analyzed: the virtual environment as a means of pedagogical interaction and written communicative competence as an expression of students’ expressive development. Data were collected through systematic observation during the implementation of the learning sessions, and written performance was assessed using a previously validated analytical rubric. To guide the analysis, one general hypothesis and four specific hypotheses were formulated, allowing the study to examine the overall competence and its specific dimensions in greater depth. The data were analyzed using the Wilcoxon signed-rank test. The results showed statistically significant differences between the pretest and posttest scores, demonstrating that the use of the Second Life virtual environment had a positive influence on written communicative competence, both at the general level and in its specific components. The study concludes that Second Life represents a valuable pedagogical resource for strengthening written production and contributes relevant evidence for future educational research.
Keywords: Second Life; communicative skills; virtual reality; avatar